2011
DOI: 10.1007/s00122-011-1767-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification and comparative mapping of a powdery mildew resistance gene derived from wild emmer (Triticum turgidum var. dicoccoides) on chromosome 2BS

Abstract: Powdery mildew, caused by Blumeria graminis f. sp. tritici, is an important foliar disease of wheat worldwide. Wild emmer (Triticum turgidum var. dicoccoides) is a valuable genetic resource for improving disease resistance in common wheat. A powdery mildew resistance gene conferring resistance to B. graminis f. sp. tritici isolate E09 at the seedling and adult stages was identified in wild emmer accession IW170 introduced from Israel. An incomplete dominant gene, temporarily designated MlIW170, was responsible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…We further determined the chromosomal location of 5 polymorphic ESTs (Table S1), and there were complete differences in the genomic and chromosomal locations using the Chinese Spring nullisomic-tetrasomic lines compared to those using in silico mapping. However, in the past, ESTs were believed to be conserved portions of expression genes, which are used as the theoretical basis for comparative genomics analyses (Liu et al 2012). This result warns plant breeders and researchers that the homology analysis and comparative genomics analysis results are not reliable.…”
Section: Discussionmentioning
confidence: 99%
“…We further determined the chromosomal location of 5 polymorphic ESTs (Table S1), and there were complete differences in the genomic and chromosomal locations using the Chinese Spring nullisomic-tetrasomic lines compared to those using in silico mapping. However, in the past, ESTs were believed to be conserved portions of expression genes, which are used as the theoretical basis for comparative genomics analyses (Liu et al 2012). This result warns plant breeders and researchers that the homology analysis and comparative genomics analysis results are not reliable.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative genomics analyses can be used to exploit the syntenic relationships among grass species for development of new markers linked to genes of interest by analyzing well-assembled genome sequence information available in model species [7], [62]. Nevertheless, many studies have reported poor levels of micro-colinearity between wheat and rice because of inversions, deletions, duplications, and other rearrangements [6], [7], [48], [63].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, many studies have reported poor levels of micro-colinearity between wheat and rice because of inversions, deletions, duplications, and other rearrangements [6], [7], [48], [63]. The isolation of the wheat disease resistance genes Lr10 , Lr21 and Pm3 has also shown that wheat and rice have very limited colinearity in the relevant chromosomal regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These provide new opportunities for genome analysis and gene mapping. For example, Yr26 (Zhang et al 2013), Ml3D232 (Liu et al 2012), Eps-3A m (Gawroński and Schnurbusch 2012), PmAS846 (Xue et al 2012), and Pm6 (Qin et al 2011), have been finely mapped based on collinearity between wheat, rice and Brachypodium.…”
Section: Introductionmentioning
confidence: 99%